Clean and Healthy Lifestyle During the Covid-19 Pandemic in Preschool Children in Bulukumba District - Esse Puji Pawenrusi; Nurleli Nurleli; Ade Isfi Hayatu Ulfa (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
School-age children are a critical age group, because at that age children are vulnerable to health problems. Data from the Covid-19 Handling Task Force shows that 777 children aged 0-18 years died due to exposure to Covid-19. In addition, the highest mortality rate is in the 0-2 year age group (0.71%), the 16-18 year age group (0.18%) and the 3-6 year age group (0.15%). To prevent the transmission of Covid-19, the government issued regulations related to the implementation of Clean and Healthy Lifestyle during the Covid-19 period. The purpose of the study was to determine the description of clean and healthy living behavior during the covid-19 pandemic in preschool children. This research is descriptive research. The population in this study were preschoolers. The sample is 49 students, with the sampling technique using total sampling. The results showed that the habit of wearing masks, healthy latrines, clean water, physical activity and consuming nutritious food was more in the never category, namely 25 (51.0%), 41 (83.6%), 48 (97.9%) , 30 (61.2%), and 34 (69.4%). The habit of washing hands, throwing garbage in its place, brushing teeth, consuming more deworming drugs with the occasional category of 28 (57.1%), 29 (59.2%), 29 (59.2%), and 49 ( 100%), while the habit of guarding is rarely more in the never category, namely 44 (89.7%). The conclusions of the research are the habit of wearing masks, healthy latrines, clean water, physical activity and consuming nutritious food is good, while the habits of washing hands, throwing garbage in its place, brushing teeth, consuming deworming drugs are in the category of occasional, but students have a habit of not never keep your distance. It is recommended that schools and parents continue to teach Clean And Healthy Lifestyle to students as an effort to prevent the transmission of COVID-19.